2011
DOI: 10.1208/s12249-011-9669-z
|View full text |Cite
|
Sign up to set email alerts
|

Inline Real-Time Near-Infrared Granule Moisture Measurements of a Continuous Granulation–Drying–Milling Process

Abstract: Abstract. The purpose of this research was to use inline real-time near-infrared (NIR) to measure the moisture content of granules manufactured using a commercial production scale continuous twin-screw granulator fluid-bed dryer milling process. A central composite response surface statistical design was used to study the effect of inlet air temperature and dew point on granule moisture content. The NIR moisture content was compared to Karl Fischer (KF) and loss on drying (LOD) moisture determinations. Using m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
32
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 71 publications
(34 citation statements)
references
References 13 publications
1
32
0
Order By: Relevance
“…Chablani et al [34] mounted an NIR probe in the granule-transfer module, which is situated just after the fluid-bed dryer, hence evaluating the dried granules. Two PLS models were constructed where the NIR spectra were regressed against the moisture content of the granules determined via Karl Fischer (KF) titration and "loss on drying", respectively.…”
Section: Twin-screw Granulationmentioning
confidence: 99%
“…Chablani et al [34] mounted an NIR probe in the granule-transfer module, which is situated just after the fluid-bed dryer, hence evaluating the dried granules. Two PLS models were constructed where the NIR spectra were regressed against the moisture content of the granules determined via Karl Fischer (KF) titration and "loss on drying", respectively.…”
Section: Twin-screw Granulationmentioning
confidence: 99%
“…Bakeev (7) has provided a recent compilation of PAT spectroscopic process analysis techniques. Our laboratory has reported the use of inline real-time near-infrared granule moisture content (8) and focused beam reflectance measurement particle size determination (9) for a commercial scale continuous granulation-drying-milling process. Previous studies have shown that LIF can be used in pharmaceutical blending to determine the blending end point (1,10).…”
Section: Introductionmentioning
confidence: 99%
“…: Schematic diagram of industrial granulation systems operated in a continuous production line [10].…”
mentioning
confidence: 99%
“…wetting and nucleation), some 7 empirical expressions are included in the model (leading to so-called semi-empirical or "grey box" models) 8 in order to allow simulation of the granulation system. 9 Although the underlying mechanisms of the granulation process are still being investigated, especially in 10 case of TSG where such detailed knowledge is not yet established [3], it is well motivated to model the 11 system at meso-or macro-scale such as to exploit the benefits of process system engineering (PSE) methods 12 and tools [16]. PSE tools rely on domain knowledge and mathematical and experimental techniques to build 13 computer models which relate the change at a molecular level to macro-scale system performance in order 14 to develop and optimise the system.…”
mentioning
confidence: 99%
See 1 more Smart Citation